2020
DOI: 10.1002/da.23120
|View full text |Cite
|
Sign up to set email alerts
|

The psychiatric sequelae of the COVID‐19 pandemic in adolescents, adults, and health care workers

Abstract: Background: The COVID-19 pandemic is the most serious global public health crisis since the 1918 influenza pandemic. This study is the first to assess its mental health impact across the lifespan in the United States in adolescents, adults, and health care workers. Methods: We recruited 4909 participants through an online survey advertising on Facebook and Instagram to assess exposure to COVID-19 and psychiatric symptoms from April 27 to July 13. We also recruited through the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
219
3
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(245 citation statements)
references
References 29 publications
9
219
3
14
Order By: Relevance
“…Furthermore, the effect of the pandemic on mental health and substance use is likely to be more pronounced among other subgroups, such as youth living in poverty or with preexisting mental health conditions. With research rapidly emerging on these important issues, 2,3,6,29 more targeted interventions can be developed to mitigate the negative impact of the pandemic on adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the effect of the pandemic on mental health and substance use is likely to be more pronounced among other subgroups, such as youth living in poverty or with preexisting mental health conditions. With research rapidly emerging on these important issues, 2,3,6,29 more targeted interventions can be developed to mitigate the negative impact of the pandemic on adolescent mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic and the restrictions implemented to prevent and contain its transmission have caused widespread disruptions in the lives of adolescents and their families. 1 Initial findings on adolescent mental health during COVID-19 indicate cause for concern, with study findings suggesting an increase in depressive symptoms [2][3][4][5][6] (particularly in adolescent girls 2,[7][8][9] ) and alcohol consumption. 10 However, the rapidly accumulating evidence on the effect of COVID-19 on adolescent mental health has been limited by use of convenience samples and inadequate baseline measures to accurately capture the pandemic's unfolding impact.…”
Section: Introductionmentioning
confidence: 99%
“…Many infected HCWs also struggle to return to their ordinary life after COVID-19 infection because they suffer from physical disability, low energy, cognitive symptoms, and affective symptoms [5,6]. Furthermore, some infected HCWs may develop suicidal ideation after a full recovery from COVID-19 [7].…”
Section: Introduction 1frontline Health Care Workers In Covid-19 Pandemicmentioning
confidence: 99%
“…Although epidemics do not necessarily affect adolescent suicidality 8 , admissions data from hospitals in the United States, Europe, and the Middle East show an increase in self-harm, suicidal ideation, and suicide attempts during the COVID-19 pandemic 21,22 . In addition, an online survey conducted during the pandemic revealed that 37% of adolescents reported having suicidal ideation 23 .…”
Section: Introductionmentioning
confidence: 99%